Denaturing mass photometry for rapid optimization of chemical protein-protein cross-linking reactions - Gizardin-Fredon, Hugo (2024)
Funding Information: This work was supported by the CNRS, the University of Strasbourg, Lorraine University, the \u201CAgence National de la Recherche\u201D (ANR-16-CE11-0032-04 snoRNP assembly; ANR-23-CE44-0035 NAProt-XLMS) and the French Proteomics Infrastructure (ProFI; ANR-10-INBS-08-03). H.G.F. acknowledges the French Ministry for Education and Research for funding of his PhD. This work was funded by Funda\u00E7\u00E3o para a Ci\u00EAncia e Tecnologia/Minist\u00E9rio da Ci\u00EAncia, Tecnologia e Ensino Superior (FCT/MCTES, Portugal) through national funds to iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020) and the Associate Laboratory LS4FUTURE (LA/P/0087/2020). Publisher Copyright: © The Author(s) 2024.